Treatment of palm oil mill secondary effluent using solar fenton oxidation processes [electronic resource] - 209315 Muhamad Fahmi Shaari; Fakulti Kejuruteraan Awam (2007)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Alam Sekitar)) - Universiti Teknologi Malaysia, 2007